Students’ Understanding of Student Well-Being: A Case Study - Falkenberg, Thomas; Ukasoanya, Grace; Krepski, Heather (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2022)
What does it mean for students to flourish (to be well) in school, what school ecology would this require, and what capabilities to live a flourishing life should schools help students develop? In this paper, we report on a study that inquired into these three questions – from the perspective of the students themselves, which is a perspective rarely inquired into. Data were collected from students at a large high school in Canada, using a survey (N=50) and focus group interviews (N=24). The findings provide diverse and rich student perspectives that in some respect complement adult perspectives on student well-being.